PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI KEMAMPUAN METAKOGNISI SISWA DALAM MENYELESAIKAN SOAL CERITA - Mailah, Siti; Sujarwo, Imam (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
Understanding mathematical concepts is an important aspect in achieving optimal mathematics learning outcomes. Understanding mathematical concepts is also an important foundation for thinking in solving mathematical problems and everyday problems. Students can easily solve math problems if they understand the concepts well. One of the mathematical abilities that plays an important role in understanding concepts is the ability of metacognition. With the ability of metacognition, students can easily control and regulate what is learned. So this study aims to describe the understanding of mathematical concepts in terms of students' metacognition ability in solving story problems. This study used qualitative research methods with a phenomenological approach. The subjects in this study amounted to 6 grade VII students of SMP Negeri 4 Malang and the subject retrieval technique used purposive sampling. The data collection techniques used are tests and interviews, while to find out the validity of using triangulation techniques. The results of this study show: 1) students with high metacognition ability meet all indicators of instrumental understanding and complete relational understanding and students are able to explain the reasons for the answers obtained so that they are classified as having relational understanding. 2) Students with moderate metacognition ability are able to meet the instrumental comprehension indicator while for the relational comprehension indicator there are two indicators that can be met but are lacking and three indicators have not been met, and students are able to explain the reasons for some of the answers given, so they are classified as having instrumental understanding that is skewed towards relational understanding. 3) students with low metacognition ability are only able to meet the indicators Instrumental understanding and does not meet all indicators of relational understanding and students have not been able to explain the answers obtained so they are classified as having instrumental understanding. ABSTRAK Pemahaman konsep matematis menjadi aspek penting dalam mencapai hasil belajar matematika yang optimal. Pemahaman konsep matematis juga merupakan landasan penting untuk berpikir dalam menyelesaikan permasalahan matematika maupun permasalahan sehari-hari. Siswa dapat mudah menyelesaikan masalah matematika jika telah memahami konsep dengan baik. Salah satu kemampuan matematika yang berperan penting terhadap pemahaman konsep adalah kemampuan metakognisi. Dengan adanya kemampuan metakognisi, siswa dapat dengan mudah mengontrol dan mengatur apa yang dipelajari. Sehingga penelitian ini bertujuan untuk mendeskripsikan pemahaman konsep matematis ditinjau dari kemampuan metakognisi siswa dalam menyelesaikan soal cerita. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan fenomenologis. Subjek dalam penelitian ini berjumlah 6 siswa kelas VII SMP Negeri 4 Malang dan teknik pengambilan subjek menggunakan purposive sampling. Teknik pengumpulan data yang digunakan adalah tes dan wawancara, sedangkan untuk mengetahui keabsahan data menggunakan triangulasi teknik. Hasil penelitian ini menunjukkan: 1) siswa dengan kemampuan metakognisi tinggi memenuhi semua indikator pemahaman instrumental dan pemahaman relasional secara lengkap serta siswa mampu menjelaskan alasan dari jawaban yang diperoleh sehingga tergolong memiliki pemahaman relasional. 2) siswa dengan kemampuan metakognisi sedang mampu memenuhi indikator pemahaman instrumental sedangkan untuk indikator pemahaman relasional terdapat dua indikator yang dapat dipenuhi tetapi kurang dan tiga indikator belum terpenuhi, serta siswa mampu menjelaskan alasan dari sebagian jawaban yang diberikan, sehingga tergolong memiliki pemahaman instrumental yang condong pada pemahaman relasional. 3) siswa dengan kemampuan metakognisi rendah hanya mampu memenuhi indikator pemahaman instrumental dan tidak memenuhi semua indikator pemahaman relasional serta siswa belum mampu menjelaskan atas jawaban yang diperoleh sehingga tergolong memiliki pemahaman instrumental.